2018
DOI: 10.5114/aoms.2016.61031
|View full text |Cite
|
Sign up to set email alerts
|

Stool antigen detection versus 13 C-urea breath test for non-invasive diagnosis of pediatric Helicobacter pylori infection in a limited resource setting

Abstract: IntroductionThe prevalence of childhood infection with Helicobacter pylori is high, especially in developing countries. Non-invasive methods for detection of infection in children should be inexpensive, easy to perform, well tolerated and have a high diagnostic accuracy. We aimed to compare the reliability, specificity and sensitivity of the H. pylori stool antigen (HpSA) test with the 13C-urea breath test (13C-UBT) for the diagnosis of H. pylori infection in a limited resource setting.Material and methodsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
0
29
0
2
Order By: Relevance
“…In other hand, Sykora [20] found the prevalence of H. pylori infection in asymptomatic children in the Czech Republic at a rate of 7%. Recent studies conducted by several researchers reported different ranges of H. pylori infection; Daugule et al, [221] in Latvia confirmed that (17.7%) of the total 220 patient samples was positive to SAT; in Korea Moon et al, [22] reported that from 318 seropositive subjects, 256 (80.5%) showed positive stool test; El-shabrawi et al, [23] in Egypt, reported that the H. pylori SAT test was positive in 34 (89.5%) out of the 38 patients.…”
Section: Prevalence Of H Pylori In Females According To Habitation Sitementioning
confidence: 99%
“…In other hand, Sykora [20] found the prevalence of H. pylori infection in asymptomatic children in the Czech Republic at a rate of 7%. Recent studies conducted by several researchers reported different ranges of H. pylori infection; Daugule et al, [221] in Latvia confirmed that (17.7%) of the total 220 patient samples was positive to SAT; in Korea Moon et al, [22] reported that from 318 seropositive subjects, 256 (80.5%) showed positive stool test; El-shabrawi et al, [23] in Egypt, reported that the H. pylori SAT test was positive in 34 (89.5%) out of the 38 patients.…”
Section: Prevalence Of H Pylori In Females According To Habitation Sitementioning
confidence: 99%
“… 24 The reduction a dose of 50 mg in children was found in several studies that have been used to diagnose H. pylori infection. 22 , 25 At the same dose of 13 C-urea, low production of endogenous CO 2 in younger children has a relatively high isotope ratio of 13 CO 2 to 12 CO 2 . 25 However, in Indonesia we use a similar dose for adults and children.…”
Section: Urea Breath Testmentioning
confidence: 99%
“…Development of an accurate rapid SAT could make diagnosis of the infection easier and cheaper, especially for low‐income countries; therefore, studies evaluated the accuracy of fast SATs in different settings. A rapid lateral flow one‐step H. pylori SAT was evaluated against UBT in 60 symptomatic children (mean age 7.2 years), showing a rather good overall accuracy of 91.7% . Although the sensitivity, specificity, and positive predictive value were 89.5% (95% CI: 75.2‐97.1), 95.5% (95% CI: 77.2‐99.9), and 97.1% (95% CI: 85.1‐99.9), respectively, the negative predictive value was only 84% (95% CI: 63.9‐95.5).…”
Section: Diagnosismentioning
confidence: 99%